Algebraic foundations in computer science : essays dedicated to symeon bozapalidis on the occasion of his retirement - Kuich, Werner , 1941-; Rahonis, George (Lecture notes in computer science, 2011)
This collection of 15 papers honors the career of Symeon Bozapalidis. The focus is on his teaching subjects: algebra, linear algebra, mathematical logic, number theory, automata theory, tree languages and series, algebraic semantics, and fuzzy languages